Enhanced Adsorption of Mercury(II) Ions from Aqueous Solution by Carbon-Based Adsorbents Containing Cl-, S- and N-functional Groups - Jianzhong Zhu; Baolin Deng; John Yang (Adsorption Science & Technology)
Mercury (Hg) is a highly toxic metal which occurs in surface and ground waters as the Hg 2+ ion. The aim of the present study was to develop carbon-based adsorbents that contain chlorine (Cl), sulphur (S) or nitrogen (N) functional groups in an attempt to enhance the removal of Hg 2+ ions from aqueous environments. Thus, activated carbon (AC) was oxidized by treatment with nitric acid and then with thionyl chloride, followed by reaction with ethylenediamine, dithio-oxamide and 1,2-ethanedithiol, respectively. Such chemically-modified activated carbons were characterized by scanning electron microscopy in conjunction with energy-dispersive spectroscopy (SEM–EDS), Fourier-transform infrared (FT-IR) spectroscopy and potentiometry. Batch experiments to study the kinetics and equilibrium of Hg 2+ ion adsorption were performed to evaluate the efficacy of the functionalized carbon adsorbents. Sample characterizations indicated that chlorine, sulphur or nitrogen functional groups were effectively immobilized onto the activated carbon surface, thereby generating more negative surface charges favouring cation adsorption. Adsorption kinetics and equilibrium experiments showed that Hg 2+ ion adsorption by activated carbons modified with ethylenediamine (ACNN), dithio-oxamide (ACNS) and 1,2-ethanedithiol (ACSS) was fast (e.g. ACNN < 30 min) and had a high capacity (e.g. ACNN =/> 200%) over AC. The adsorptive capacity decreased in the order ACNN (120 mg/g) > ACSS (105 mg/g) > ACNS (90 mg/g) > AC (60 mg/g), suggesting a high Hg 2+ ion affinity for the modified carbons.